1988
DOI: 10.1111/j.1528-1157.1988.tb03749.x
|View full text |Cite
|
Sign up to set email alerts
|

Combined Administration of Carbamazepine and Phenobarbital: Effect on Anticonvulsant Activity and Neurotoxicity

Abstract: Despite the trend towards single drug therapy of epilepsy, patients resistant to monotherapy are commonly treated with more than one antiepileptic drug. As part of an investigation on the experimental background for antiepileptic drug combinations, the effect of the pharmacodynamic interactions between carbamazepine and phenobarbital on the toxicity/efficacy ratio was studied in mice. All results were expressed in terms of drug concentrations in the brain to exclude possible pharmacokinetic interactions from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 23 publications
2
21
0
1
Order By: Relevance
“…In light of these facts, the synergistic 3-drug interaction of CBZ, PB and TPM should be compared with three 2-drug interactions between CBZ + TPM, PB + TPM and CBZ + PB. The isobolographic analysis of the 2-drug combination of CBZ with PB revealed that this combination produced additive interaction in the mouse MES model [32] . In the case of 2-drug combinations of CBZ with TPM and PB with TPM, experiments in vivo study revealed that TPM used at a sub-protective dose of 5 mg/ kg significantly potentiated the anticonvulsant action of CBZ and PB in the mouse MES model [33] .…”
Section: Discussionmentioning
confidence: 99%
“…In light of these facts, the synergistic 3-drug interaction of CBZ, PB and TPM should be compared with three 2-drug interactions between CBZ + TPM, PB + TPM and CBZ + PB. The isobolographic analysis of the 2-drug combination of CBZ with PB revealed that this combination produced additive interaction in the mouse MES model [32] . In the case of 2-drug combinations of CBZ with TPM and PB with TPM, experiments in vivo study revealed that TPM used at a sub-protective dose of 5 mg/ kg significantly potentiated the anticonvulsant action of CBZ and PB in the mouse MES model [33] .…”
Section: Discussionmentioning
confidence: 99%
“…However, pharmacodynamic interactions are more difficult to identify and measure than pharmacokinetic interactions and are often only concluded by default when a pharmacokinetic interaction has been ruled out. Animal studies have provided useful evidence of pharmacodynamic interactions involving AEDs (18)(19)(20)(21)(22), and results from in vitro studies are promising (23), although there is still little evidence of the applicability of such interactions in humans (24). However, anecdotal evidence and clinical experience has shown that some combinations of AEDs are more effective in controlling seizures than either drug used alone, and such combinations will be used despite a lack of scientific evidence to explain the favourable drug interaction; examples of these AED combinations include VPA and ethosuximide (ESM) (25), clonazepam (CZP) plus VPA (26), and CBZ plus VPA (27,28).…”
Section: Pharmacodynamic Interactionsmentioning
confidence: 99%
“…Pharmacodynamic interactions are difficult to prove and often are uncovered in the course of common clinical practice. However, some investigations performed using models of epilepsy seem to substantiate their existence [47][48][49][50][51][52]. Pharmacodynamic interactions usually enhance toxicity, but can either enhance or reduce efficacy.…”
Section: Hidden Interactionsmentioning
confidence: 95%